2022
DOI: 10.1097/qad.0000000000003462
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory biomarker profiles and cardiovascular risk in individuals with and without HIV

Abstract: Background:People with HIV have an increased risk for cardiovascular morbidity and mortality. Inflammation and immune activation may contribute to this excess risk.Methods:We assessed thirty-one biomarkers in a subset of POPPY participants and identified three distinct inflammatory profiles: ‘gut/immune activation’, ‘neurovascular’, and ‘reference’ (relatively low levels of inflammation). Ten-year cardiovascular disease (CVD) risk predictions were calculated using the QRISK, Framingham Risk Score (FRS) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Individuals under cART experience serious non-AIDS events (SNAEs), such as non-AIDS malignancies, cardiovascular events, renal and hepatic diseases, bone disorders, and neurocognitive impairment [6][7][8]. SNAEs are considered the main causes of morbidity and mortality among PLWH in the cART era [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals under cART experience serious non-AIDS events (SNAEs), such as non-AIDS malignancies, cardiovascular events, renal and hepatic diseases, bone disorders, and neurocognitive impairment [6][7][8]. SNAEs are considered the main causes of morbidity and mortality among PLWH in the cART era [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic aberrant inflammation and intestinal bacterial translocation contribute to atherosclerosis, tumor development, and liver fibrosis [7][8][9][10]. Elevated levels of biomarkers associated with chronic inflammation and bacterial translocation increase the risk of cardiovascular diseases and malignancies, sharing similar pathophysiological mechanisms with the general population but not identical ones [3,4,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in life expectancy among PLWH, the number of people over 50 years of age increases [ 2 ] which leads to an increase in age-related comorbidities. [ 3 ]. A plethora of mechanisms contribute to the pathogenesis of non-HIV-related diseases in HIV patients [ 3 ], and inflammation plays a central role [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The REPRIEVE study showed distinct differences in inflammatory and immune proteomic profiles in PWH with subclinical coronary artery disease characterized by coronary plaque vs. coronary artery calcium deposition [18]. Refinements to the tentatively defined clusters of Sukumaran et al [19] based on much larger numbers could prove valuable in discriminating among subpopulations who might best benefit from targeted interventions mitigating specific inflammatory profiles, as well as optimize their preventive care. They may also assist in defining the role of inflammation in other non-AIDS causes of morbidity and mortality in PWH, such as chronic kidney disease (CKD).…”
mentioning
confidence: 98%
“…But which specific cellular-and cytokine-based biomarkers might help guide interventions remains uncertain [2,[16][17][18]. Sukumaran et al [19] sought to address this knowledge gap by assessing 31 inflammatory biomarkers in a crosssectional study of 312 participants, 70% of whom were PWH. Ten-year CVD risk predictions calculated by QRISK score were examined across three different proinflammatory profiles they constructed: 'gut/immune activation', 'neurovascular', and 'reference'.…”
mentioning
confidence: 99%